Factors associated with effective coverage of child health services in Burkina Faso. Issue 11 (10th September 2018) - Koulidiati, Jean‐Louis; De Allegri, Manuela; Souares, Aurelia; Ouedraogo, Samiratou; Hien, Hervé; Robyn, Paul Jacob; Brenner, Stephan
Summary: Objective: To identify factors associated with both crude and effective health service coverage of under‐fives in rural Burkina Faso. Methods: In a cross‐sectional study, 494 first‐line health facilities, 7347 households and 12 497 under‐fives were surveyed. Two sequential logistic random effects models were conducted to assess factors associated with crude and effective coverage. Results: Of 614 children under‐five with a reported illness episode, 427 (69.5%) received care at a health facility. Of those, 274 (64.1%) received care at a health facility providing at least the minimum threshold of service quality. We found that younger age, having a severe illness, shorter distance between household and health facility, and being from wealthier households were positively associated with crude coverage. In addition, low patient caseload and longer consultation had a positive association, while frequent facility supervisions had a negative association with effective coverage. Moreover, the nurse to clinical staff ratio at the health facility was positively associated with both crude and effective coverage. Conclusion: Our study found that crude coverage is associated with pre‐disposing and enabling factors of health care access, while the availability of nurses is a strong predictor for both crude and effective coverage. This suggests that in the context of scarcity of resources, investing in human resources in health sector could be one of the priorities for decision‐makers to ensure children in need not only access to healthcare but also good quality of care.